Postępowanie o udzielenie zamówienia publicznego w procesie współdziałania podmiotów publicznych i prywatnych w sferze gospodarki komunalnej - Guziński, Maciej (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
Cooperation of public and private entities in the sphere of municipal services may take the form of: commissioning private entities to perform construction works, provide supplies, services; delegating the exercise of the communal tasks. Selection of contractors to perform these tasks takes place within the framework of apublic contract, aimed at preserving the rules of fair competition, equal treatment of economic operators, which secures cooperation of public and private entities in this respect.
Keywords: gospodarka komunalna; postępowanie o udzielenie zamówienia publicznego; podmioty publiczne; podmioty prywatne; współdziałanie